Market planning for preparatory launch of the iQue drink. - Low, Yao Ming. (2008)
The report detailed the market planning for the preparatory launch of a new beverage, the iQue drink. A specific marketing plan was designed mainly to improvise the product in terms of content as well as packaging to appeal to the intended market and to build brand awareness through a series of advertisements as well as sales promotions. Research from taste tests and interviews with retailers together with mass surveys form the basis of our report.